Subcutaneous cardioverter-defibrillator, patient selection, implantation, postoperative management in the Krasnoyarsk - A. V. Prokopenko; E. A. Ivanitskiy (Российский кардиологический журнал, 2022)
This article describes the patient selection procedure for subcutaneous cardioverter-defibrillator implantation, the implantation technique, and the features of postoperative follow-up of patients, the features of programming at all stages of patient treatment.